Comparison of Structural Architecture of HCV NS3 Genotype 1 versus Pakistani Genotype 3a. (21st October 2014) - Fatima, Kaneez; Azhar, Esam; Mathew, Shilu; Damanhouri, Ghazi; Qadri, Ishtiaq
Abstract : This study described the structural characterization of Pakistani HCV NS3 GT3a in parallel with genotypes 1a and 1b NS3. We investigated the role of amino acids and their interaction patterns in different HCV genotypes by crystallographic modeling. Different softwares were used to study the interaction pattern, for example, CLCBIO sequence viewer, MODELLER, NMRCLUST, ERRAT score, and MODELLER. Sixty models were produced and clustered into groups and the best model of PK-NCVI/Pk3a NS3 was selected and studied further to check the variability with other HCV NS3 genotypes. This study will help in future to understand the structural architecture of HCV genome variability and to further define the conserved targets for antiviral agents.